2021
DOI: 10.1186/s13068-021-01938-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of simultaneous uptake of xylose and glucose in Caldicellulosiruptor kronotskyensis for optimal hydrogen production

Abstract: Background Caldicellulosiruptor kronotskyensis has gained interest for its ability to grow on various lignocellulosic biomass. The aim of this study was to investigate the growth profiles of C. kronotskyensis in the presence of mixtures of glucose–xylose. Recently, we characterized a diauxic-like pattern for C. saccharolyticus on lignocellulosic sugar mixtures. In this study, we aimed to investigate further whether C. kronotskyensis has adapted to uptake glucose in the disaccharide form (cellob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, a study of sugar uptake in C . kronotskyensis revealed that it possesses better uptake kinetics for xylose and cellobiose than for glucose and it showcased that it is a promising candidate for hydrogen production [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a study of sugar uptake in C . kronotskyensis revealed that it possesses better uptake kinetics for xylose and cellobiose than for glucose and it showcased that it is a promising candidate for hydrogen production [ 13 ].…”
Section: Introductionmentioning
confidence: 99%